THE LANGUAGE INTERFERENCE IN ENGLISH CONVERSATION AT PONDOK PESANTREN FADHLUL FADHLAN SEMARANG DUE TO THE ADDITION OF JAVANESE PARTICLES - Rizqiyah, Silvy Milchatir; Firmonasari, Aprillia (Lire Journal (Journal of Linguistics and Literature), 2024)
This research aimed to describe (1) the form and function of Javanese particles in English conversations; and explained the factors behind the occurrence of language interference through the addition of Javanese particles to English conversations by students at the Fadhlul Fadhlan Islamic boarding school in Semarang. This research included field research with a qualitative approach and was presented descriptively. The data for this research was in the form of oral speech from the data source of students at the Fadhlul Fadhlan Islamic Boarding School when they were in the Islamic boarding school environment. The data collection technique method used non-participant observation by observing students' conversations and then taking notes and structured interviews with 27 students. The data analysis technique method used three stages, namely data reduction, data presentation, and concluding. The interference theory by weinrich is to identify the interference phenomena. The results of this research showed that there were two types of Javanese particles added by students in English conversations, namely the single Javanese particles and the combination of Javanese particles. The second result was there were two forms of interference were found, namely grammatical interference and lexical interference. Third, the factors that caused interference through the addition of particles were internal factors in the form of bilingualism, lack of mastery of English grammar and vocabulary, and being carried away by mother tongue habits. Furthermore, external factors were the environment, facilitating communication between students, situations, and conditions